Daily and seasonal mitochondrial protection: Unraveling common possible mechanisms involving vitamin D and melatonin. Issue 199 (May 2020) - Mocayar Marón, Feres José; Ferder, León; Reiter, Russel J.; Manucha, Walter
Abstract: From an evolutionary point of view, vitamin D and melatonin appeared very early and share functions related to defense mechanisms. In the current clinical setting, vitamin D is exclusively associated with phosphocalcic metabolism. Meanwhile, melatonin has chronobiological effects and influences the sleep-wake cycle. Scientific evidence, however, has identified new actions of both molecules in different physiological and pathological settings. The biosynthetic pathways of vitamin D and melatonin are inversely related relative to sun exposure. A deficiency of these molecules has been associated with the pathogenesis of cardiovascular diseases, including arterial hypertension, neurodegenerative diseases, sleep disorders, kidney diseases, cancer, psychiatric disorders, bone diseases, metabolic syndrome, and diabetes, among others. During aging, the intake and cutaneous synthesis of vitamin D, as well as the endogenous synthesis of melatonin are remarkably depleted, therefore, producing a state characterized by an increase of oxidative stress, inflammation, and mitochondrial dysfunction. Both molecules are involved in the homeostatic functioning of the mitochondria. Given the presence of specific receptors in the organelle, the antagonism of the renin-angiotensin-aldosterone system (RAAS), the decrease of reactive species of oxygen (ROS), in conjunction with modifications in autophagy and apoptosis, anti-inflammatory properties inter alia, mitochondria emerge as the final common target for melatonin and vitamin D. The primary purpose of this review is to elucidate the common molecular mechanisms by which vitamin D and melatonin might share a synergistic effect in the protection of proper mitochondrial functioning.